Mixed convection in a PCM filled cavity under the influence of a rotating cylinder - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2020)
In this study, mixed convection in a phase change material filled square cavity under the effect of a rotating cylinder was numerically investigated. The vertical walls are kept at constant temperatures while the horizontal walls are adiabatic. The effects of angular rotational speed of the cylinder (between -7.5 and 7.5), vertical location of the cylinder (between 0.25 and 0.75) and two different cylinder sizes (0.05 and 0.1) on the fluid flow and heat transfer were numerically investigated in detail. It was observed that rotating cylinder parameters can be used to control the heat transfer and melting process in the cavity. For angular rotational speed of cylinder at (omega = 7.5) compared to motionless cylinder (omega = 0), average heat transfer enhances by about 22.50%. The highest value of the average heat transfer for different vertical locations of the cylinder depends on the angular rotational speed of the cylinder. The average Nusselt number increases 10% when a large cylinder is used compared to smaller one for clockwise rotation of the cylinder and it is 19.8% for the stationary cylinder configuration.
Keywords: PCM; Rotating cylinder; Finite element method; Mixed convection